Pembuatan Sistem Kebakaran Ruang Server Berbasis Web pada DISKOMINFO Kota Makassar - Wahyu Hidayat M; Khairul Imam MJ; Jumadil Ahmad Safii; Muhammad Alif Leo; Ahmad Faris Al Faruq (Sakura Publisher, 2023)
Development of Web-Based Fire Alarm System in Server Room at Diskominfo Makassar City. Diskominfo Makassar City is an institution that carries out some of the regional government affairs of Makassar City in the field of communication and informatics. Makassar City Diskominfo has a server room to handle services in the communications and informatics sector for sub-districts and villages in Makassar City. Making a web-based fire alarm is intended as a form of meeting server room security standards in terms of fire threats that can occur at any time and helping to supervise or monitor the server room. The working method or procedure for making this tool goes through the stages of analysis, design, implementation, and testing. The main components needed consist of a KY026 fire sensor, MQ2 sensor, ESP8266 microcontroller, and Laravel 7. This fire alarm tool utilizes Internet of Things (IoT) technology so that the tool can be connected to web applications. This tool detects indications of fire based on the flame wave indicator and carbon monoxide gas through the KY026 flame sensor and MQ2 sensor. Users of this tool will receive email notifications if there is a fire in the server room. It is easy for users to monitor server rooms by accessing web applications built using Laravel 7. This website is still local and can be accessed via a search engine with the address 192.168.43.244. This tool is expected to minimize damage and accelerate the handling of fire incidents in the server room. Testing of this tool was carried out on two components, namely the KY026 fire sensor and the MQ2 sensor. Based on the results of the tests that have been carried out, both components are able to detect fire indicators at certain distances. This is proven by the user receiving a fire notification when the component detects a wave of fire or carbon monoxide gas and the user can monitor the condition of the server room in real time.